2022
DOI: 10.3390/cells11213420
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Neutrophil Extracellular Traps (NETs) Expression and Primary Graft Dysfunction Following Human Lung Transplantation

Abstract: Primary graft dysfunction (PGD) is characterized by alveolar epithelial and vascular endothelial damage and inflammation, lung edema and hypoxemia. Up to one-third of recipients develop the most severe form of PGD (Grade 3; PGD3). Animal studies suggest that neutrophils contribute to the inflammatory process through neutrophil extracellular traps (NETs) release (NETosis). NETs are composed of DNA filaments decorated with granular proteins contributing to vascular occlusion associated with PGD. The main objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
(87 reference statements)
2
5
0
Order By: Relevance
“…Similar results were published by Bonneau et al. ( 29 ) that reported higher circulating inflammatory cytokines (IL-6 and IL-8) and NETosis biomarkers in the setting of primary graft dysfunction after lung transplantation. In fact, although NETosis and NET generation are important for preventing pathogen invasion, their excessive formation can result in a slew of negative consequences, such as autoimmunity, inflammation and tissue damage ( 30 32 ).…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were published by Bonneau et al. ( 29 ) that reported higher circulating inflammatory cytokines (IL-6 and IL-8) and NETosis biomarkers in the setting of primary graft dysfunction after lung transplantation. In fact, although NETosis and NET generation are important for preventing pathogen invasion, their excessive formation can result in a slew of negative consequences, such as autoimmunity, inflammation and tissue damage ( 30 32 ).…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of plasma samples at individual time points revealed over 15 analytes were significantly different between PGD+ and PGD-patients. Several of these, including IL-6 and MCP-1, align with plasma biomarkers of PGD+ previously reported, while others are original findings (Hoffman et al 2009;Bharat et al 2008;Shah et al 2012;Bonneau et al 2022;Moreno et al 2007). Of note, BCA-1 (CXCL13) and IL-22 were significantly elevated in PGD+ plasma compared to PGD-plasma in a multivariate analysis of all time points analyzed.…”
Section: Discussionsupporting
confidence: 80%
“…In a recent study, we found that patients undergoing lung transplants with stage 3 primary graft dysfunction (PGD3) had increased NETosis biomarkers (MPO-DNA, MPO, and cfDNA) and pro-inflammatory cytokines (IL-8 and IL-6) correlating with severe graft dysfunction. In addition, as depicted by immunofluorescence staining, we observed in some of the lung graft tissues prior to transplantation, microvascular occlusion mainly derived from neutrophils undergoing NETosis and platelet-bound neutrophils adhered onto lung endothelium 34 .…”
Section: Discussionmentioning
confidence: 72%